Development Strategy of Integrated Farming System (Beef Cattle, Rice, Corn) on Suboptimal Land: Minahasa Regency - Jolyanis Lainawa; Eusebius K. M. Endoh; Zadrak M. Warouw (International Journal of Applied Business and International Management, 2025)
Suboptimal land in Minahasa Regency has strong potential for integrated cattle–rice–corn farming, but production inefficiency and limited managerial capacity still hinder its performance. This study aims to evaluate technical efficiency, competitiveness, and strategic development priorities for the integrated system on suboptimal land in Minahasa. SFA and DEA are used to measure technical efficiency, while the PAM assesses comparative and competitive advantages. SWOT analysis, the IE Matrix, and the QSPM are applied to formulate strategic directions. Primary data were collected from 90 farmer–breeders representing traditional, semi-commercial, and commercial business types. The findings show an average technical efficiency of 0.72, indicating a 28% improvement potential. The cattle–corn system has a stronger comparative advantage (DRCR 0.79) than cattle–rice (DRCR 0.82), although both face private competitiveness constraints (PCR 1). SWOT–IE results place the system in Quadrant V (“Hold and Maintain”), with QSPM prioritizing efficiency enhancement, institutional strengthening, waste-based downstream product development, and risk adaptation. The integrated system can become an efficient and competitive sustainable agriculture model with adequate institutional support and technological innovation.